2016
DOI: 10.1111/ehr.12326
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in economic inequality: lessons from colonial Botswana, 1921–74

Abstract: This article contributes to the growing literature on colonial legacies influencing long‐term development. It focuses on Botswana, a case where the post‐independence diamond‐led economy has been considered an economic success story, despite its high levels of inequality. Here it is argued that this pathway of rapid resource‐driven growth combined with increasing socio‐economic inequality had already started during the time of the colonial cattle economy, and that this older case is equally relevant for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…While some argue that sub-Saharan African societies became unequal as a consequence of colonization, others suggest that they were characterized by relatively very high inequality also in earlier epochs. This might still be due to contact with the Europeans through the slave trade, but in such case colonialism played at most a secondary role in enrooting inequality as well as under-development (for a synthesis of the debate, Acemoglu and Robinson 2010; Bolt and Hillbom 2016) A quickly-expanding, recent literature on African economic history has gone a long way towards providing better estimates of key economic variables, like per-capita GDP, for many parts of the continent. Although much remains to be done, these studies are beginning to change the very empirical basis upon which discussion of the "African divergence" takes place (Prados de la Escosura 2012; Austin and Broadberry 2014;Broadberry and Gardner 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some argue that sub-Saharan African societies became unequal as a consequence of colonization, others suggest that they were characterized by relatively very high inequality also in earlier epochs. This might still be due to contact with the Europeans through the slave trade, but in such case colonialism played at most a secondary role in enrooting inequality as well as under-development (for a synthesis of the debate, Acemoglu and Robinson 2010; Bolt and Hillbom 2016) A quickly-expanding, recent literature on African economic history has gone a long way towards providing better estimates of key economic variables, like per-capita GDP, for many parts of the continent. Although much remains to be done, these studies are beginning to change the very empirical basis upon which discussion of the "African divergence" takes place (Prados de la Escosura 2012; Austin and Broadberry 2014;Broadberry and Gardner 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, extractive institutions established by the colonizers in Africa have often been blamed as one of the causes of current underdevelopment (Acemoglu, Johnson, and Robinson 2001;Acemoglu and Robinson 2012;Nunn 2008). In addition, by favoring the interests of European companies and settlers with respect to those of the majority of the African population, government institutions are frequently thought to have heavily affected the distribution of income and wealth in African societies (Acemoglu, Johnson, and Robinson 2005;Bolt and Hillbom 2016). If similar extractive institutions persisted over time, we may be able to identify the roots of current inequality by looking at patterns of income distribution during the colonial period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 That phases of pre-industrial economic expansion and rising inequality can go hand in hand was also shown for colonial Botswana. 5 Additionally, new evidence on long term inequality trends for Portugal suggests that early modern phases of economic contraction led to diminishing levels of inequality. 6 On the other hand, recent research across late medieval and early modern Europe has suggested that inequality tended to rise also in the absence of economic growth or during periods of economic decline, underlining the complexity of the relationship between growth and inequality.…”
mentioning
confidence: 99%